Severe Tuberculous Meningitis with Fatal Consequences in a Pediatric Patient: A Case Report - Qadree, Abdul Khalid; Chaudhary, Sachin Mahendrakumar; Emmanuel Kelechi, Anasonye; Pandey, Sushmita; Dhakal, Sandesh (Clinical Medicine And Health Research Journal, 2023)
Background: Tuberculous meningitis is a critical public health issue in underdeveloped nations due to its high morbidity and death. Tuberculous meningitis with non-specific symptoms of the central nervous system in children needs to be assessed with great vigilance as delay in diagnosis results in poor prognosis. Case Report: We present a case of 20 months old female child with symptoms of sensory alteration, aberrant movements, and fever. Lumbar puncture findings indicated cell count of 1121/mm3, reduced glucose level, and elevated proteins. Ventriculomegaly with diffuse hypodenseimages in the frontal and paraventricular regions with areas of ischemia and hydrocephalus were evident in the MRI. Neuroinfection was indicated with images compatible with obstructive hydrocephalus of early evolution suggestive of tuberculous meningitis. The patient was started on 2HRZE/10 hr regimen. However, the patient was observed with significant neurological sequel and presented multiple comorbidities despite supportive measures. Conclusion : Children are more susceptible to tuberculous meningitis than adults and result in death and disability, if not diagnosed early. Hence, the physicians must always be on the alert for tuberculous meningitis, especially in the areas where tuberculosis is endemic